1979
DOI: 10.1042/bj1770729
|View full text |Cite
|
Sign up to set email alerts
|

The direct radioimmunoassay of oestrogen glucuronides in human female urine

Abstract: Radioimmunoassays for five oestrogen metabolites in urine are described; they are oestrone 3-glucuronide, oestradiol 3-glucuronide, oestradiol 17 beta-glucuronide, oestriol 3-glucuronide and oestriol 16 alpha-glucuronide. These assays have proved accurate and reliable and can be performed rapidly; they have been carried out directly in diluted menstrual cycle urine and pregnancy urine. No sample pretreatment was required. Preliminary results suggest that clinically useful information can be obtained by perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…34-36 The E1G assay developed by O'Connor and colleagues captures meaningful patterns of change with respect to reproductive aging as demonstrated in prior studies of the menopausal transition 37,38 The assay is described in full elsewhere. 38 Measures of urinary E1G in our sample are expressed in ng/mg creatinine.…”
Section: Methodsmentioning
confidence: 99%
“…34-36 The E1G assay developed by O'Connor and colleagues captures meaningful patterns of change with respect to reproductive aging as demonstrated in prior studies of the menopausal transition 37,38 The assay is described in full elsewhere. 38 Measures of urinary E1G in our sample are expressed in ng/mg creatinine.…”
Section: Methodsmentioning
confidence: 99%
“…Urinary E1G was measured by a competitive enzyme immunoassay (EIA) that cross-reacts 83% with estradiol glucuronide, thus measuring both estradiol and estrone in glucuronide forms 29. Baker and colleagues30 found that 17<beta>-estradiol-3-glucuronide is excreted in urine across the menstrual cycle in the same pattern as E1G with a clear mid-cycle peak but at concentrations 5 times lower than E1G. The E1G assay developed by O’Connor and colleagues captures meaningful patterns of change with respect to reproductive aging as demonstrated in prior studies of the menopausal transition31 The assay is described in full elsewhere 29,32…”
Section: Methodsmentioning
confidence: 99%
“…All details including validation of the procedure were published [40]. Urinary “immunoreactive” estriol-3-glucuronide (E3-3G), a biomarker of enterohepatic circulation of estrogens, was determined by radioimmunoassay as described [41] using reagents kindly provided by Drs A. Kellie and P. Samarajeewa. This estriol conjugate is formed exclusively in the mucosal cells of the intestine and thereafter excreted without further metabolism in the urine and may, therefore, serve as a biomarker of the reabsorption of biliary estrogens in the intestine.…”
Section: Methodsmentioning
confidence: 99%